2018
DOI: 10.1128/msphere.00097-18
|View full text |Cite
|
Sign up to set email alerts
|

Influential Parameters for the Analysis of Intracellular Parasite Metabolomics

Abstract: Molecular characterization of pathogens such as the malaria parasite can lead to improved biological understanding and novel treatment strategies. However, the distinctive biology of the Plasmodium parasite, including its repetitive genome and the requirement for growth within a host cell, hinders progress toward these goals. Untargeted metabolomics is a promising approach to learn about pathogen biology. By measuring many small molecules in the parasite at once, we gain a better understanding of important pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Lack of an effective enrichment method for ring stage Plasmodium has led to considerable host-contributed noise in samples, limiting the success of sensitive downstream analyses such as proteomics and metabolomics. Specifically, our previous work demonstrated that characteristics of the erythrocyte batch contributed to the resultant ring parasite metabolome as heavily as drug treatment 17 . Additionally, erythrocyte noise stymied previous ring stage metabolomics and proteomics experiments as parasite-derived signals could not reliably be determined over the host erythrocyte contribution 15,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Lack of an effective enrichment method for ring stage Plasmodium has led to considerable host-contributed noise in samples, limiting the success of sensitive downstream analyses such as proteomics and metabolomics. Specifically, our previous work demonstrated that characteristics of the erythrocyte batch contributed to the resultant ring parasite metabolome as heavily as drug treatment 17 . Additionally, erythrocyte noise stymied previous ring stage metabolomics and proteomics experiments as parasite-derived signals could not reliably be determined over the host erythrocyte contribution 15,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The inability to enrich for ring stage parasites has exacerbated host contamination of samples and limited our ability to discern interesting parasites phenotypes (18,21). Successful ring stage enrichment will beneficially reduce contribution of non-parasite factors not only for metabolomics studies, but for a variety of ring stage related experiments.…”
Section: Discussionmentioning
confidence: 99%
“…We previously explored parameters important for metabolomics studies of P. falciparum (21). Not surprisingly, the metabolomes of non-enriched ring stage samples were heavily influenced by host erythrocyte contamination (about a third of 375 total metabolites detected were associated with the blood cells used for parasite propagation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major contaminating DNA source that we detected in our samples was from humans ( Figure 574 2A). This was not surprising given that, in our experimental system, the culture and host 575 environments are rich in human DNA [79,80,91]. It is also possible that human DNA was 576 introduced during the single cell isolation or WGA steps [55].…”
mentioning
confidence: 93%